The loss of glacier resilience due to climate change throughout the Cordillera Blanca, Peru between 1984 and 2023 - Giraldo Malca, Ulises Francisco (2025)
The loss of mountain glaciers has accelerated in recent decades, linked to global warming, which in Peru alone has caused the loss of more than half of its glaciated area in fifty years. The Cordillera Blanca is the highest and most extensively glacierized tropical mountain range in the world, and glacier-fed streams provide water for hundreds of thousands of people living downstream. Previous inventories and glacier-specific mass balance studies have documented persistent and sustained mass loss. Yet the range-wide resilience of glaciers – the capacity to accumulate annual snowfall to offset area loss – remains an unquantified variable that is important to understand the evolution and climate response of glaciers over time and better project future mass changes for the coming decades. Therefore, we analyze the relationship between the annually clean glacier area and snow cover fluctuations and climate variability throughout the entire glacierized Cordillera Blanca between 1984 and 2023. To this end, we used multispectral Landsat imagery to identify clean glaciers and distinguish accumulation areas by calculating the Normalized Water Differential Index. The results show a 44 % reduction in glacier area, reflected in a decrease from the pre-2013 annual average of 54,469 ha to 42,700 ha in subsequent years. Our results suggest glaciers have passed a significant mass balance threshold, such that since 2012, glaciers have lost their ability to regain mass. We also document a strong inverse correlation of glacier area with the increase in global mean temperature, with the greatest loss occurring during the lasts strong El Niño-Southern Oscillation (ENSO) phases. We conclude that glaciers have become less resilient over the past decade, that the deglaciation of the Cordillera Blanca is primarily driven by increasing average temperatures and that the glaciers with the greatest retreat are those with perimeters proportionally more exposed to other types of surfaces (i.e., bedrock or lakes),.